CERN Large Hadron Collider (LHC) Radiation Source for Magnetic Resonance Biospectroscopy in Metabolic and Molecular Imaging and Diagnosis of Cancer - Alireza, Heidari; Zahra, Torfeh; Sophia, Iorgulescu; Olivia, Robinson; Lin, Hu; Charlotte, Vauclin; Schiltz, Natalie; Scarlett, Sondermann; Lucy, MacLennan; Julia, Smith; Lydia, Williamson (Journal of New Developments in Chemistry, 2022)
Molecular imaging is a new method in examining physiological studies in molecular dimensions. Among the various methods that have been introduced for this purpose, the magnetic resonance spectroscopy (MRS) method has made it possible to more accurately study the activities of the brain region as well as tumors in different parts of the body. MRS imaging is a type of non– invasive imaging technique that is used to study metabolic changes in the brain, stroke, seizure disorders, Alzheimer's disease, depression and also metabolic changes in other parts of the body such as muscles. In fact, since metabolic changes in the human body appear faster than anatomical and physiological changes, the use of this method can play an important role in the early detection and diagnosis of cancers, infections, metabolic changes and many other diseases. Graphical abstract: CERN Large Hadron Collider (LHC) radiation source for magnetic resonance biospectroscopy in metabolic and molecular imaging and diagnosis of cancer.
Keywords: CERN; Large Hadron Collider (LHC); Radiation Source; Magnetic Resonance Biospectroscopy; Metabolic and Molecular Imaging; Diagnosis of Cancer